IMPROVING ELEMENTARY SCHOOL STUDENTS' INTEREST IN LEARNING THROUGH THE USE OF AUDIO-VISUAL MEDIA IN SCIENCE LESSONS - Riska Arista; Pratiwi Dwi Warih Sitaresmi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to examine the extent to which the use of audio-visual media can increase elementary school students' interest in learning Natural and Social Sciences (IPAS). The background of the study began with low student engagement during the learning process, which still focused on conventional methods. This study used a descriptive qualitative approach , with research subjects including teachers and fifth-grade students of SDN Tunggak Cerme. Data were collected through observations of learning activities, in-depth interviews, and review of learning documents, then analyzed using the Miles and Huberman model which includes the stages of data reduction, data presentation, and drawing conclusions. The results showed that the use of audio-visual media was able to foster focus, increase activeness, and build positive attitudes in students towards IPAS learning. Students appeared more enthusiastic, participated in discussions, and more easily understood the material through interesting videos and animations. Teachers considered this media effective in creating a fun and interactive learning atmosphere. However, obstacles were also found such as limited technological facilities, lack of training for teachers, and minimal support from school policies. Thus, the success of implementing audio-visual media is greatly influenced by the creativity of educators, the readiness of facilities, and support from educational institutions. Overall, this study concludes that the use of audio-visual media has great potential in increasing students' interest in learning and is a strategic step towards more innovative and meaningful science learning in elementary schools